2021
DOI: 10.1002/rmv.2217
|View full text |Cite
|
Sign up to set email alerts
|

Role of p38 mitogen‐activated protein kinase signalling in virus replication and potential for developing broad spectrum antiviral drugs

Abstract: Summary Mitogen‐activated protein kinases (MAPKs) play a key role in complex cellular processes such as proliferation, development, differentiation, transformation and apoptosis. Mammals express at least four distinctly regulated groups of MAPKs which include extracellular signal‐related kinases (ERK)‐1/2, p38 proteins, Jun amino‐terminal kinases (JNK1/2/3) and ERK5. p38 MAPK is activated by a wide range of cellular stresses and modulates activity of several downstream kinases and transcription factors which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 187 publications
0
37
0
Order By: Relevance
“…Initially we observed a switch on/off phenomenon in the hnRNPA1 expression levels Inhibitors that block the m6A pathway would target cellular factors (47), therefore the emergence of drug-resistant viral mutants would seem to be unlikely in epidrugs (28,(48)(49)(50)(51)(52)(53)(54)(55). However, since such drugs would also inhibit the epitranscriptomic modification of cellular mRNAs, they may lead to toxicity (48) and should be used for treating the acute infections.…”
Section: Discussionmentioning
confidence: 99%
“…Initially we observed a switch on/off phenomenon in the hnRNPA1 expression levels Inhibitors that block the m6A pathway would target cellular factors (47), therefore the emergence of drug-resistant viral mutants would seem to be unlikely in epidrugs (28,(48)(49)(50)(51)(52)(53)(54)(55). However, since such drugs would also inhibit the epitranscriptomic modification of cellular mRNAs, they may lead to toxicity (48) and should be used for treating the acute infections.…”
Section: Discussionmentioning
confidence: 99%
“…The requirement of the cellular factors is usually conserved among multiple strains of a particular virus or even across multiple members of a given virus family ( Chander et al, 2021 ; Khandelwal et al, 2020 ; Kumar et al, 2011a , 2011b , 2019 ). We demonstrated in vitro antiviral efficacy of DZNep (inhibitor that targets cellular factor-methyl transferase) against both wild-type and Delta strains of SARS-CoV-2, besides demonstrating it's protective effect against lethal IBV ( Coronaviridae family member) infection in embryonated chicken eggs suggesting a broad-spectrum antiviral effect.…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/Akt signaling pathway plays a core role in cell physiology and pathology and participates in key cellular processes, such as glucose homeostasis, lipid metabolism and protein synthesis by mediating growth factor signals 51 . MAPK family members are key kinases involved in most signal transduction pathways, are activated by a wide range of cellular stresses, and regulate the activity of some downstream kinases and transcription factors 52 . A large number of studies have shown that the PI3K/Akt and MAPK signaling pathways, upstream of Nrf2, are also involved in the activation of the Nrf2 pathway.…”
Section: Discussionmentioning
confidence: 99%